Towards Urban Zero-waste Community through Bulk Stores: Challenges and Opportunities - Mada Sophianingrum (Waste Technology, 2020)
Zero-waste is a recent phenomenon which is one of the most cost-effective local solution to handle some of the environmental, social and economic challenge in urban area. Urbanization and rising populations will affect the increase in consumption, which in turn will also increase waste production in urban areas. In 2020, it was noted that 24 percent of waste in Indonesia had not been processed properly. Thus, the waste management approach needs to prioritize not only through a qualified technology system but also needs to be supported by the transformation of people's behavior, one of which is through zero-waste. Bulk store is an urban initiative that applies the concept of zero-waste. This shop combines social and entrepreneurial concepts as well as the environment in carrying out its business processes. Through the concept of zero-waste, people must bring their own containers to shop here. This study aims to examine the opportunities and challenges of bulk store as an initiative to achieve zero-waste communities in urban areas. The method used in this research is qualitative approach through interviews and observations with shop owners, consumers and networks. The results obtained from this study are that education is the main factor determining the success of the bulk store. Apart from that, bulk stores also have another role, namely as a market-hub for local producers around urban areas. This makes bulk stores have a strategic role in supporting the zero-waste community